2013
DOI: 10.1590/abd1806-4841.20131888
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical efficacy of superficial peeling with 85% lactic acid versus 70% glycolic acid

Abstract: BACKGROUND:Peeling is a procedure which aims to accelerate the process of skin exfoliation.OBJECTIVES Development of formulations containing lactic acid at 85% or glycolic acid at 70% and the evaluation of these formulations on clinical efficacy in reduction of fine wrinkles. METHODS Preliminary stability tests were carried out and an in vivo study was performed with three groups with 9 representatives each. One was the control group, which used only sunscreen; another one used lactic acid+sunscreen, and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A randomized controlled trial was performed on 27 patients FST II-IV receiving 3 procedures either containing 70% GA, 85% lactic acid or sunscreen as a control at monthly intervals for periorbital wrinkles. The study ultimately found that both GA and LA could significantly improve wrinkling after 3 procedures (p<0.005) [70].…”
Section: Glycolic Acidmentioning
confidence: 85%
“…A randomized controlled trial was performed on 27 patients FST II-IV receiving 3 procedures either containing 70% GA, 85% lactic acid or sunscreen as a control at monthly intervals for periorbital wrinkles. The study ultimately found that both GA and LA could significantly improve wrinkling after 3 procedures (p<0.005) [70].…”
Section: Glycolic Acidmentioning
confidence: 85%
“…Noteworthy studies have demonstrated the effectiveness of AHAs in addressing these concerns. In a randomized clinical trial conducted by Prestes et al [12], the application of 70% glycolic acid and 85% lactic acid in monthly peels exhibited notable efficacy in diminishing fine wrinkles. Moreover, a recent clinical trial by Narda et al [13] revealed a significant increase in total collagen levels following the administration of glycolic acid, providing compelling evidence for its beneficial effects in skin rejuvenation and establishing its potential as a valuable therapeutic agent in dermatology.…”
Section: Efficacy Of Topical Aha Formulationsmentioning
confidence: 99%
“…Lactic Acid (LA): Lactic acid (as sodium lactate) is a well-known part of the skin's natural moisturizing complex, and is considered to be an excellent moisturizer.LA also contributes to the cell cycle in human keratinocytes [107].Treatment with 12% LA resulted in increased epidermal and dermal firmness and thickness and clinical improvement in skin smoothness and in the appearance of lines and wrinkles.Both the lactic and glycolic acid peelings were effective in reducing fine wrinkles on the external-lateral region of the eyes, after three applications (85% LA versus 70% GA) [109]. Recently more attention has been drawn to alpha hydroxy and polyhydroxy acids (AHA and PHA) due to their excellent moisturizing and antioxidant properties.Algiert-Zielińska et.al, 2019 reported maintenance of the epidermal barrier integrity during application of lactic acid (LA) and lactobionic acid and the opportunity to use them on sensitive skin types including couperose skin [112].…”
Section: B α-Hydroxy Acids (Ahas)mentioning
confidence: 99%